Effects of simulated spectral holes on speech intelligibility and spatial release from masking under binaural and monaural listening - Garadat, Soha N. (Acoustical Society of America, 2010)
The possibility that “dead regions” or “spectral holes” can account for some differences in performance between bilateral cochlear implant (CI) users and normal-hearing listeners was explored. Using a 20-band noise-excited vocoder to simulate CI processing, this study examined effects of spectral holes on speech reception thresholds (SRTs) and spatial release from masking (SRM) in difficult listening conditions. Prior to processing, stimuli were convolved through head-related transfer-functions to provide listeners with free-field directional cues. Processed stimuli were presented over headphones under binaural or monaural (right ear) conditions. Using Greenwood’s [(1990). J. Acoust. Soc. Am. 87, 2592–2605] frequency-position function and assuming a cochlear length of 35 mm, spectral holes were created for variable sizes (6 and 10 mm) and locations (base, middle, and apex). Results show that middle-frequency spectral holes were the most disruptive to SRTs, whereas high-frequency spectral holes were the most disruptive to SRM. Spectral holes generally reduced binaural advantages in difficult listening conditions. These results suggest the importance of measuring dead regions in CI users. It is possible that customized programming for bilateral CI processors based on knowledge about dead regions can enhance performance in adverse listening situations.